Model Pembelajaran Kooperatif Tipe Make A Match Untuk Meningkatkan Hasil Belajar Kimia Siswa Kelas X Pada Materi Hidrokarbon SMA Negeri 1 Dolo - Elvian Togagu; Suherman Suherman; I Made Tangkas (Universitas Tadulako, 2014)
Hydrocarbon is one of the chemical topics that is taught in grade X in senior high school.This topic consisted of carbon (C) and hydrogen (H) elements in the discussion process. The objective of this research was to improve the students’ learning outcomes of grade X by applying cooperative learning model make a match type in chemistry subject, with hydrocarbon material at SMA Negeri 1 Dolo in the academic year 2012/2013. The subjects of this research were the students of grade XA with the total number of 26 students. The instruments used in this research were pre-test, post-test which consist of 16 questions and observation sheets. From the students’test results; it was found that there were 23% students were in low category. After the researcher applied the cooperative learning model with Make A Match type in the first cycle, the percentage of the students’ classical completeness reached to 73%, with the classical absorption of 77% in good category. In the second cycle, the percentage of the students’ classical completeness was 96% with the classical absorption percentage of 84% which is in very good category. It could be seen from the outcomes that after cooperative learning model make a match type applied, there was an improvement in the percentage of the students’ learning outcomes.